Exploring the Role of Artificial Intelligence in Education, Students Preferences and Perceptions - Anna Ayu Herawati; Syamsu Yusuf; Ilfiandra Ilfiandra; Agus Taufik; Ahmad Syaf Ya Habibi (STAI Hubbulwathan Duri, 2024)
The development of AI technology has opened new opportunities for the delivery and reception of education. Therefore, a profound understanding related to students' perspectives, expectations, and concerns regarding the utilization of AI in the learning process becomes a crucial aspect. This study explores the perceptions of university students in Indonesia towards the use of Artificial Intelligence (AI) in education. A quantitative descriptive survey was conducted involving 200 students from the Faculty of Teacher Training and Education at Bengkulu University. The instrument used is a student perception scale about AI adapted from Buabbas et al. (2023). Data analysis used descriptive analysis and Chi-Square test. The findings indicate that most students have a positive view of the use of AI in learning, seeing it as a tool that can enrich their learning experience and increase access to educational resources. However, concerns were also raised about the replacement of teachers' roles by AI, the loss of human elements in learning interactions, and data privacy issues. The study concludes that while AI has great potential to transform education, a careful, human-centered approach that involves the active role of teachers and safeguards students' privacy and data security is necessary. Further research is recommended to provide more comprehensive information about the impacts and benefits of the emergence of AI in education.